The representative claim - Saward, Michael, 1960- (Oxford : Oxford University Press, 2010)
'The Representative Claim' is set to transform our core assumptions about what representation is and can be. At a time when political representation is widely believed to be in crisis, the book provides a critical corrective to conventional wisdom on the present and potential future of representative democracy.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Representative government and representation; Democracy